Nanoparticle-mediated CRISPR/dCas9a activation of multiple transcription factors to engineer insulin-producing cells. Issue 9 (15th February 2023) - Lee, Mei-Hwa; Thomas, James L.; Lin, Chien-Yu; Li, Yi-Chen Ethan; Lin, Hung-Yin
Abstract : Four gRNAs were synthesized and used to form ribonucleoproteins (RNPs) with tracRNA and dCas9-VPR, and were then immobilized on magnetic peptide-imprinted chitosan nanoparticles, which enhanced transfection for production of insulin. Abstract : Insulin may help to control blood glucose levels in diabetes; however, the long-term release of insulin is important for therapy. In this work, four guide RNAs (gRNA) for factors that promote specification and maturation of insulin-producing cells were synthesized: pancreatic and duodenal homeobox 1 (PDX1), protoendocrine factor (neurogenin 3, NGN3), NK6 homeobox 1 (NKX6.1), and musculoaponeurotic fibrosarcoma oncogene family A (MAFA). These gRNAs were used to form ribonucleoproteins (RNPs) with tracRNA and dCas9-VPR, and were then immobilized on magnetic peptide-imprinted chitosan nanoparticles, which enhanced transfection. The production and release of insulin from transfected cells were then measured using ELISA and staining with anti-insulin antibodies. The expression of the genes was evaluated using qRT-PCR; this was also used to investigate the cascade of additional transcriptional regulators. The magnitude and duration of insulin production were evaluated for single and repeated transfections (using different transfection schedules) to identify the most promising protocol.